Survivin regulates chromosome segregation by modulating the phosphorylation of Aurora B during porcine oocyte meiosis. Issue 21 (17th November 2018) - Chen, Li; Yin, Tailang; Nie, Zheng-Wen; Wang, Tao; Gao, Ying-Ying; Yin, Shu-Yuan; Huo, Li-Jun; Zhang, Xia; Yang, Jing; Miao, Yi-Liang
ABSTRACT: SURVIVIN is an essential chromosomal passenger complex (CPC) subunit and participates in cell division. In this study, we used porcine oocyte as a model to investigate the roles of Survivin during porcine oocyte maturation. Survivin was highly expressed in germinal vesicle (GV) and germinal vesicle breakdown (GVBD) stages oocytes, mainly localized in the GV at GV stage and on the chromosomes after GVBD. We have used RNA interference to specifically deplete Survivin in oocytes during in vitro maturation (IVM). Immunofluorescence assay showed that Survivin -depleted oocytes failed to produce polar body in meiosisⅠ (failed to complete cytokinesis), and they were arrested in metaphaseⅠwith misaligned chromosomes. The homologous chromosomes in Survivin -depleted oocytes could not be separated normally. Moreover, both the phosphorylation levels of Aurora B and the mRNA level of Mad2L1 related to spindle assembly checkpoint (SAC) was decreased in Survivin -depleted oocytes, which thus inhibited the degradation of Cyclin B1 ( CCNB1 ) to complete meiosis. Taken together, we conclude that Survivin is an important mediator of centromere and midbody docking of Aurora-B as well as its activity and regulates SAC and MPF activity during meiosis in porcine oocytes.